EFEITO DA ÉPOCA DE COLHEITA NA QUALIDADE DO ARROZ DE TERRAS ALTAS SUBMETIDO À PARBOILIZAÇÃO - GARCIA, Diva Mendonça (2009)
This work aimed the evaluation of the effect of the harvest time and the parboiling in the physical, chemical and sensory quality of the upland rice. The BRS Primavera and BRS Sertaneja were harvested on the 30th. and 47th. days after the flourishing (DAF). Parboiling processes were done with the absorption of 28 and 30% moisture, with pre-defined times. The concentration of total solids, soaking water pH, rice final moisture content in paddy, and the opening of grains were analyzed. The quality of the milling rice was explored in relation to the yield of whole grains, degrees of milling, classification of the grain defects, color evaluation, viscosity profile, gelatinization temperature, amylose content, centesimal composition and mineral content. Sensory aspects were also evaluated, among them, the texture and stickiness of the milling and parboiled cooked grains. The acceptance of the parboiled rice, and the profile of the testers. There was a significant interaction (P ≤ 0,05) between the cultivar and the moisture content to the total solid concentration and soaking water pH. The final moisture content did not show differences (P > 0,05) in relation to the two harvest times, and the higher the soaking time, the higher the opening of grains at the parboiling process. The yield of whole grains result is higher for the cultivars harvest on the 30th. DAF than for the one on the 47th. DAF. The parboiling lessens the degree of milling, despite of the harvest time, and when it happens with delay, it rises the level of defects. The percentage of grains not gelatinised was lessened as higher the soaking time, despite of the time of the harvest and cultivar. The BRS Primavera cultivar and the treatments harvested on the 30th. DAF showed a lighter grain coloration, with no having differences (P > 0,05) between the parboiling treatments, according to the moisture content. The results of the viscosity profile showed significant differences (P ≤ 0,05) between the processing types. There was not a significant difference for the protein content, however, to the content of lipids, ash and crude fiber the values were higher for the parboiled rice than for the milling rice. The phosphorus, potassium and copper content are present in higher amounts in the treatment of parboiled rice. The cultivars are suitable to the parboiling industry, despite the time of the harvest, and are sensory accepted, reinforcing that a strict and intense control must be done during the process